Metagenomic Analysis of the Microbial Communities and Resistomes of Veal Calf Feces - Salaheen, Serajus; Kim, Seon Woo; Hovingh, Ernest; Van Kessel, Jo Ann S.; Haley, Bradd J. (Frontiers in Microbiology, 2021)
Antimicrobial resistance (AMR) is a major public health concern, and dairy calves, including veal calves, are known reservoirs of resistant bacteria. To investigate AMR in the fecal microbial communities of veal calves, we conducted metagenomic sequencing of feces collected from individual animals on four commercial veal operations in Pennsylvania. Fecal samples from three randomly selected calves on each farm were collected soon after the calves were brought onto the farms (n = 12), and again, just before the calves from the same cohorts were ready for slaughter (n = 12). Results indicated that the most frequently identified phyla were Firmicutes, Bacteroidetes, Proteobacteria, and Actinobacteria. Fecal microbial communities in samples collected from the calves at the early and late stages of production were significantly different at the genus level (analysis of similarities [ANOSIM] on Bray-Curtis distances, R = 0.37, p < 0.05), but not at the phylum level. Variances among microbial communities in the feces of the younger calves were significantly higher than those from the feces of calves at the late stage of production (betadisper F = 8.25, p < 0.05). Additionally, our analyses identified a diverse set of mobile antimicrobial resistance genes (ARGs) in the veal calf feces. The fecal resistomes mostly consisted of ARGs that confer resistance to aminoglycosides, tetracyclines, and macrolide-lincosamide-streptogramin B (MLS), and these ARGs represented more than 70% of the fecal resistomes. Factors that are responsible for selection and persistence of resistant bacteria in the veal calf gut need to be identified to implement novel control points and interrupt detrimental AMR occurrence and shedding.